2023
DOI: 10.3389/fimmu.2023.1171898
|View full text |Cite
|
Sign up to set email alerts
|

The oral microbiome of patients with ischemic stroke predicts their severity and prognosis

Abstract: Background and objectivesStroke is a common group of cerebrovascular diseases that can lead to brain damage or death. Several studies have shown a close link between oral health and stroke. However, the oral microbiome profiling of ischemic stroke (IS) and its potential clinical implication are unclear. This study aimed to describe the oral microbiota composition of IS, the high risk of IS, and healthy individuals and to profile the relationship between microbiota and IS prognosis.MethodsThis observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The community DNA fragments were paired with paired-end sequencing using an Illumina platform (Illumina, San Diego, CA, USA). The raw sequencing data was processed and analyzed on the QIIME2 analysis platform (Sun et al 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…The community DNA fragments were paired with paired-end sequencing using an Illumina platform (Illumina, San Diego, CA, USA). The raw sequencing data was processed and analyzed on the QIIME2 analysis platform (Sun et al 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, many of the oral pathogenic bacteria in the saliva that are swallowed and transmitted to the gut can affect ischemic stroke [ 115 ]. Wu et al recruited observational studies on three groups of subjects (IS, high-risk IS [HRIS] and healthy control [HC]) and found that HRIS and the oral salivary microbial group of IS subjects had a high diversity and predictive value in the severity and prognosis of IS [ 108 ]. Therefore, oral microflora may serve as a potential biomarker for patients with IS.…”
Section: Prognostic Markers Of Ais In Other Body Fluidsmentioning
confidence: 99%
“…In an animal experiment, mice receiving intragastric administration of salivary microbiota from periodontitis patients stimulated migration of interleukin-17A-producing cells from the gut to the brain and resulted in significantly poorer stroke outcomes [ 29 ]. Recently, the oral bacterial genera Streptococcus , Prevotella , Veillonella , and Fusobacterium from saliva samples were shown to be associated with ischemic stroke [ 30 ]. However, these studies on ischemic stroke tended to rely on small cohorts or data based on 16S rRNA gene sequencing.…”
Section: Introductionmentioning
confidence: 99%